ANALISIS LAYANAN BIMBINGAN KONSELING DALAM KONSEP IDENTITIAS EGO DAN PERENCANAAN KARIR REMAJA - Siskha Putri Sayekti (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2024)
High school students are in the adolescent development phase with a number of life challenges to prepare themselves and face the future. Through career planning, high school students are expected to be able to identify their abilities, interests, and motivations. However, some of them face an identity crisis and have a significant impact on their trust and self-esteem. This study discusses and analyzes the strategies of counseling guidance services in supporting the formation of self-identity and career planning of adolescents. This study examines the factors that influence career planning in the context of guidance services in depth. This research method uses a study search by collecting and analyzing relevant literature. Some of the findings of this research are significant correlations between the role of counseling services in the development of ego identity and adolescent career planning at the high school level.